A utilização de objetos de aprendizagem para a compreensão e construção de gráficos estatísticos - Castro, Juscileide Braga de (2012)
The information processing is important for the citizen formation, since we are surrounded by data and facts that need to be understood. However, recent evaluations such as SAEB and INAF indicated the difficulties that children and adults from several Brazilian regions have been in the understanding of the processes related to data representation in graphs and tables, as well as understand involved mathematical concepts. Research have showed that the study of graphs by using of technological devices such as computer and another digital technologies, favoring the development of statistical concepts learning since these strategies help the visualization and exploration of many activities, providing new ways of thinking and act. Thus, the current study investigated as a didactic sequence, using learning objects (LO), could help in the understanding of concepts related to information processing as the construction and interpretation of bar and sectors graphs. The work was conducted in a Brazilian public school located in Fortaleza city using two classes of 5th grade of elementary school, with 26 students each ones. The school classes were divided in control group (CG) and experimental group (EG) and all students were previously evaluated through a pre-test. Posteriorly an intervention using a didactic sequence including mathematical aspects of graphs and tables, problem situations with classification and proportionality and research activities was performed only with EG. The GC was not exposed to any formal education beyond the classroom received. Thereafter a post test was applied to both groups (CG and EG). The data were analyzed by student performance before and after the performed activities taking into account the evolution of strategies and information processing. Was observed a improviment in the strategies used by children for GE group after intervention. These activities give the integration of different technologies employed in school curriculum (laptop and digital and analogic technologies). Thus, the use of digital technologies provided didatic experiences in processing information by students as a to visualize and simulate different situations; process information; work with real situations, with investigative contexts and explore the produced data. Therefore, the results of current study contribute to better understand the graphs learning as well as for further development of new resources and activities.